Place Attachment of Shoppers: A Study of Palms Mall, Ibadan, Nigeria - Olla, Ifeoluwa; Amole, Bayo; Amole, Dolapo (Journal of Contemporary Urban Affairs, 2023)
The shopping mall has emerged as an important component of many cities. While the rapid development of malls and the increasing patronage show their viability and acceptance by the populace, respectively, there is a dearth of studies that examine the impact of its physical and behavioural attributes on attachment. This study examines the effect of physical characteristics, activities, and socioeconomic characteristics on place attachment to the first standalone mall in Ibadan, Nigeria. From a sampling frame of 7, 115 shoppers, quantitative data was obtained from 350 respondents using systematic sampling on April 29, 2017, through a structured questionnaire. The data was analysed using mean, factor analysis, cross-tabulation, correlation, and categorical regression. The findings show that the most prevalent activities are meeting others (α = 0.77); leisure (α = 0.75); and, parties and hanging out (α = 0.70). The important physical attributes are circulation, wayfinding, and aesthetics (α = 0.87); access to mechanical conveyors, mall decoration, and quality materials (α = 0.80); and, ambience (α =0.79). However, the regression results show that the most important factors of attachment are access to mechanical conveyors, mall decoration, and quality materials (β = 0.334); leisure (β = 0.279); purchasing activities (β = 0.236); and, meeting others (β = 0.165). Hence, these factors should be considered in creating new malls in the city. In the context of urbanism, this is key to the social and economic revitalization of cities.